Endermology treatment for breast cancer related lymphedema (ELOCS): Protocol for a phase II randomized controlled trial. (October 2019) - Malloizel-Delaunay, Julie; Chantalat, Elodie; Bongard, Vanina; Chaput, Benoit; Garmy-Susini, Barbara; Yannoutsos, Alexandra; Vaysse, Charlotte
Abstract: Objectives: Secondary lymphedema is a serious and debilitating condition, which may cause a range of cutaneous, infectious and joint complications with major psychological and social consequences. There is no curative treatment available. Initial symptomatic treatment includes Intensive Decongestive Treatment (IDT), which involves the use of multi-layered compression bandages, along with manual lymph drainage, physical exercise and skin care. IDT leads to an average decrease in limb volume of 20–40%, when compared to the contralateral limb. A better reduction may be obtained through the use of new adjuvant techniques, of which endermology is an example. The aim of this phase II study is to validate an IDT protocol combining endermology with standard of care in breast cancer related lymphedema. Study design: A standardised care protocol was proposed by the University Hospital of Toulouse's Lymphology team for the treatment of upper limb lymphedema after breast cancer surgery using Cellu M6 (LPG) Endermologie over 30 min. Every patient benefitted from IDT over 5 consecutive days, within the multidisciplinary Lymphology unit. Patients were randomised into three arms as follows: Arm 1: IDT for 5 days with bandages + manual lymphatic drainage. Arm 2: IDT with bandages + manual lymphatic drainage + Cellu M6 for 5 days. Arm 3: bandages + Cellu M6 for 5 days. During the study, patients will be followed-up for a period of 6 months. Use of LPG's Cellu M6 in combination with IDT may improve upper limb volume reduction compared with standard of care. By improving breast cancer related lymphedema, we expect to minimise further fluid build-up and to improve skin care, thus reducing the number of consultations and hospital admissions caused by this condition. The results of the present research protocol are expected to promote evidence supporting the use of endermology in the field of lymphology.